(untitled) (Advances in Applied Biological Research, 2025)
Chronic kidney disease (CKD) is defined as a progressive disease that affects the overall health of kidney. CKD is diagnosed in five stages based on its symptoms and the structure and function of kidney. CKD can be significantly influenced by several lifestyle factors. Poor dietary habits, such as high intake of salt, sugar, unhealthy fats, and processed foods, contribute to obesity, hypertension, and diabetes, key risk factors for CKD. Hence, the CKD treatment requires a multifaceted approach including adopting a healthy lifestyle with a balanced diet, regular exercise, stress management, and proper hydration. This case report focuses on a 31-year-old female patient with CKD for 2 years and hypertension for 6 months who received Ayurvedic treatment at Jeena Sikho Lifecare Limited Hospital, Derabassi. The treatment method administered on her was a combination of customized Ayurveda and Panchakarma therapies, resulting in significant progresses in her symptoms, kidney health and function, and general life quality. After 7 days of IPD, the patient showed improvement in Blood Urea and Serum Creatinine, also reported relief from periorbital swelling and other symptoms. This study highlights the potential of Ayurveda as an economical alternative to conventional treatments, especially for individuals with limited financial resources who face challenges in accessing advanced healthcare. While the results are encouraging, further research with larger randomized controlled trials is essential to assess the effectiveness and safety of Ayurvedic treatments for CKD.